2018
DOI: 10.1152/jn.00548.2017
|View full text |Cite
|
Sign up to set email alerts
|

The modulation of hippocampal theta rhythm by the vestibular system

Abstract: The vestibular system is a sensory system that has evolved over millions of years to detect acceleration of the head, both rotational and translational, in three dimensions. One of its most important functions is to stabilize gaze during unexpected head movement; however, it is also important in the control of posture and autonomic reflexes. Theta rhythm is a 3- to 12-Hz oscillating EEG signal that is intimately linked to self-motion and is also known to be important in learning and memory. Many studies over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 196 publications
(221 reference statements)
1
20
0
1
Order By: Relevance
“…This corroborates a 2016 report by Hülsdünker et al 42 , showing increased theta power in the frontal, central, and parietal regions when a balance task became more challenging. This finding is also compatible with evidence that the vestibular system can modulate theta oscillation 43 .…”
Section: Discussionsupporting
confidence: 90%
“…This corroborates a 2016 report by Hülsdünker et al 42 , showing increased theta power in the frontal, central, and parietal regions when a balance task became more challenging. This finding is also compatible with evidence that the vestibular system can modulate theta oscillation 43 .…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, several studies have shown that vestibular lesions result in loss of location-specific firing of place cells, which largely reside in CA1 [ 71 , 72 ]. Further, theta rhythm, an EEG rhythm important for the coordination of place cells, has also been shown to be disrupted in CA1 and the ERC after bilateral vestibular deactivation or lesions in rats [ 73 , 74 , 75 , 76 , 77 ]. In addition, the ERC projects strongly to CA3 and CA1 of the hippocampus [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that hippocampal theta is actually linked to attention and arousal (Jacobs, Lega, & Watrous, 2017). This type of theta has been linked to sensorimotor functions (Bland & Oddie, 2001;Burgess, Barry, & O'Keefe, 2007;Ekstrom et al, 2005;Hoffman et al, 2013;Jacobs et al, 2017;Lopour, Tavassoli, Fried, & Ringach, 2013;Mormann et al, 2005;Watrous, Fried, & Ekstrom, 2011), spatial navigation (Aitken, Zheng, & Smith, 2018;Ekstrom et al, 2005;Jacobs et al, 2017;Kahana, Sekuler, Caplan, Kirschen, & Madsen, 1999;Vass et al, 2016;Watrous et al, 2011), episodic memory coding (Jacobs et al, 2017), and, of particular interest, head position all through its connection to the vestibular system (Aitken et al, 2018).…”
Section: Theta and Brain Functionmentioning
confidence: 99%
“…One of the functions of the vestibular system, specifically that of the vestibular organs within the inner ear, is to allow people to sense head acceleration; from this, the head position can then be calculated (Aitken et al, 2018). While there is currently very little research on how EEG brain waves change as head position shifts, Spironelli, Busenello, and Angrilli (2016) found that lying in a supine position correlated with decreased cortical activity and increased alpha and delta wave amplitude compared to seated position.…”
Section: Vestibular System Head Position and Theta Productionmentioning
confidence: 99%